Biochemical composition of particles shape particle-attached bacterial community structure in a high Arctic fjord. (July 2019) - Jain, Anand; Krishnan, Kottekkatu Padinchati; Singh, Archana; Thomas, Femi Anna; Begum, Nazira; Tiwari, Manish; Bhaskar, Venkateswaran Parli; Gopinath, Anu
Highlights: POM is mainly derived from autochthonous sources. POM biochemical composition strongly influence PA bacterial community composition. Complex carbohydrate degrading bacterial taxa dominates PA bacterial community. PA bacterial community can act as ecological indicator for the prevalence of complex polymeric substrates. Abstract: Kongsfjorden, a high Arctic fjord was used as a model site to test the hypothesis that source and biochemical composition of particulate organic matter (POM) exert strong selective pressure on particle-attached bacterial community than their free-living counter parts. For this subsurface water samples were collected along the particle density gradient in Kongfjorden. Microbial communities were size fractionated into free-living (FL, 0.2–3 μm) and particle-attached (PA, >3 μm), and V3-V4 16S rRNA gene amplicon sequencing was used for evaluating bacterial community composition. Further, elemental (C/N), isotopic (δ 13 C) and biochemical composition (carbohydrates, proteins and lipids) of POM were also determined. Clear niche segregation among PA and FL communities was observed, except at a location close to Open Ocean. Higher alpha diversity was recorded in majority of the PA communities as compared to the FL. δ 13 C (‰) and particulate-carbohydrate (P-CHO) content of POM strongly influence PA bacterial community composition, which was composed primarily of complex biopolymers/carbohydrates degrading bacterial taxa, in particular members of phyla Verrucomicrobia and Bacteroidetes . In addition, glacial meltwater influx and particulate organic carbon (POC) influence FL bacterial community structure. Thus, it appears that particles act as direct substrates for bacterial utilization and select particle-attached bacterial community with specific structure and function while dissolved organic carbon (DOC) plume around the particles select for some specialized free-living bacteria. Further, our results suggest that PA bacterial community can act as ecological indicator for the availability and turnover of complex polymeric substrates in high Arctic fjord environment.